2014
DOI: 10.1371/journal.pone.0103754
|View full text |Cite
|
Sign up to set email alerts
|

Task Shifting for Non-Communicable Disease Management in Low and Middle Income Countries – A Systematic Review

Abstract: BackgroundOne potential solution to limited healthcare access in low and middle income countries (LMIC) is task-shifting- the training of non-physician healthcare workers (NPHWs) to perform tasks traditionally undertaken by physicians. The aim of this paper is to conduct a systematic review of studies involving task-shifting for the management of non-communicable disease (NCD) in LMIC.MethodsA search strategy with the following terms “task-shifting”, “non-physician healthcare workers”, “community healthcare wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
405
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(416 citation statements)
references
References 35 publications
(106 reference statements)
6
405
0
5
Order By: Relevance
“…1 Task shifting rehabilitation activities to unpaid caregivers may offer a sustainable alternative to conventional rehabilitation, and provide an affordable strategy in meeting the health demands in high and LMICs. [2][3][4][5] India, with one sixth of the world's population, only has approximately 35 stroke units, located mainly in urban centres. 6,7 Consequently most people have no access to specialised stroke care and little access to conventional rehabilitation programs.…”
Section: Family-led Rehabilitation After Stroke In India: a Randomisementioning
confidence: 99%
“…1 Task shifting rehabilitation activities to unpaid caregivers may offer a sustainable alternative to conventional rehabilitation, and provide an affordable strategy in meeting the health demands in high and LMICs. [2][3][4][5] India, with one sixth of the world's population, only has approximately 35 stroke units, located mainly in urban centres. 6,7 Consequently most people have no access to specialised stroke care and little access to conventional rehabilitation programs.…”
Section: Family-led Rehabilitation After Stroke In India: a Randomisementioning
confidence: 99%
“…A 6–8 session behavioral activation treatment delivered by lay counsellors in primary health care settings in India was also cost effective, reducing depression and improving functioning in people with moderately severe to severe depression (Patel et al, 2017; Weobong et al, 2017). A systematic review of task-shifting interventions for non-communicable diseases in LMICs showed that it is potentially effective for improving access for mental healthcare (Joshi et al, 2014). …”
Section: Scaling-up Mental Health Interventions For Refugeesmentioning
confidence: 99%
“…31 Task-shifting from physicians to NPHWs, if accompanied by the restructuring of the health system, is a potentially effective and affordable strategy. 28 Specifically, successful task-shifting should include workforce skill-mix changes, worker incentives and an increase in training capacity and supportive oversight.…”
Section: Adapting Task-shifting Strategies To Non-communicable Diseasmentioning
confidence: 99%
“…8 Task-shifting strategies have the potential to meet the demands of NCD programmes since management principles for these diseases are based on screening, health promotion, initiation of treatment and referral of high-risk patients to physicians. 28 Proponents of task-shifting point to significant positive outcomes for patients with HIV, obstetric care requirements, mental health issues and malaria. 8,10,13,20 Trained 7 Task-shifting interventions by nurses and nursing assistants in LMICs have reportedly helped to reduce the burden of CVDs and there is considerable evidence supporting the effectiveness of task-shifting implementation for chronic disease management.…”
mentioning
confidence: 99%
See 1 more Smart Citation